Psychoanalytical Conflicts, Anxiety, and Ego Defense Mechanisms of The Main Character in Karin Slaughter’s The Good Daughter - Jihan Syahidah; Arido Laksono (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This study is aimed to observe the factors of defense mechanisms applied by the main character, Charlie Quinn in The Good Daughter’s novel by Karin Slaughter. The Good Daughter tells the story of Charlie Quinn who undergoes certain unfortunate situations in Pikeville, Georgia, United States. Library research is conducted to gather the data. The primary data were collected from the novel whilst the secondary data were collected from journals, books, and articles. Character and characterization, conflicts, and settings are observed for the intrinsic aspects whilst the psychology of literature approach that includes the factors of Sigmund Freud’s defense mechanisms is observed for the extrinsic aspects. It is determined that from the analysis, defense mechanisms are applied to redeem objective and neurotic anxiety. Objective and neurotic anxiety are the factors that trigger the use of defense mechanisms. Finally, the kinds of defense mechanisms employed by the main character to redeem anxiety are intellectualization, repression, denial, regression, and displacement.Keywords: The Good Daughter; defense mechanisms; objective anxiety; neurotic anxiety